Behavioural effects of PNU‐282987 and stress in an animal model of Alzheimer's disease. Issue 1 (27th January 2016) - Vicens, Paloma; Heredia, Luis; Torrente, Margarita; Domingo, José L.
Abstract: Background: Cholinergic deficits play an important role in both cognitive and behavioural alterations in Alzheimer's disease. This study was aimed at evaluating the possible therapeutic role of PNU‐282987 (PNU), an α7 nicotinic cholinergic receptor agonist, and the possible effects of stress in precipitating the onset of behavioural deficits in animals with susceptibility to Alzheimer's disease. Methods: B6C3‐Tg mice with susceptibility to Alzheimer's disease and wild‐type mice either with or without restraint stress received 0‐ or 1‐mg/kg PNU. At 12 months old, mice were evaluated for activity levels, anxiety‐like levels, and spatial learning and memory. Results: Data did not show the effects of PNU on activity and anxiety‐like behaviour. No effect of PNU on acquisition of a spatial learning task was detected, but a reversal of stress effects on retention in the Morris water maze was observed in transgenic mice. Conclusions: Further studies are needed in order to better understand the role of α7 nicotinic cholinergic receptor agonists in motor activity, anxiety, and spatial learning and memory and to develop more accurate pharmacological treatment of psychopathological diseases.